Association of exposure to phthalates and environmental phenolics with markers of kidney function: Korean National Environmental Health Survey (KoNEHS) 2015–2017. (October 2020) - Lee, Inae; Park, Jae Yoon; Kim, Sunmi; An, Jung Nam; Lee, Jeonghwan; Park, Hyunwoong; Jung, Sun Kyoung; Kim, Sung Yeon; Lee, Jung Pyo; Choi, Kyungho
Highlights: Phthalate metabolites and phenolics were associated with markers of kidney function. Covariate-adjusted standardization was used to address a potential collider issue. DEHP metabolites in urine were associated with increased ACR. Urinary MnBP, BPA, and EtP were associated with decreased eGFR. Abstract: Increasing number of consumer chemicals have been associated with chronic kidney disease (CKD) in human populations. However, many studies that investigated estimated glomerular filtration rate (eGRF) as an outcome reported inconsistent associations. In the present study, we employed a subset (n = 1292) of a nationally representative adult population participating in Korean National Environmental Health Survey (KoNEHS) 2015–2017, and assessed associations of major phthalates, bisphenol A (BPA), and parabens with both eGRF and albuminuria. In order to address a potential collider issue, a covariate-adjusted standardization method was applied, in addition to the conventional creatinine-correction, for adjusting urine dilution. Regardless of adjustment method, urinary DEHP metabolites showed significant positive associations with albumin to creatinine ratio (ACR). In addition, urinary metabolites of other heavy molecular weight phthalates such as MCOP and MCNP showed significant positive associations with ACR in the female population, but only following the covariate-adjusted standardization. For eGFR, conventional creatinine-correction resulted in positive associations with most of measured phthalate metabolites. However, with the covariate-adjusted standardization, most of positive associations with eGFR disappeared, and instead, significant negative associations were observed for MnBP, BPA, and EtP. Secondary analysis following stratification by CKD status, as well as principal component analysis (PCA), generally supported the observed associations. The present observations highlight the importance of urine dilution adjustment method for association studies on eGFR, and suggest potential effects of several consumer chemicals on adverse kidney function among humans.